2019
DOI: 10.3390/app9112216
|View full text |Cite
|
Sign up to set email alerts
|

How Working Tasks Influence Biocontamination in an Animal Facility

Abstract: The exposure to biocontaminants in animal facilities represents a risk for developing infectious, allergic and toxic diseases. The aim of this study was to determine what factors could be associated with a high level of exposure to biological agents through the measure and characterization of airborne fungi, bacteria, endotoxin, (1,3)-β-d-glucan and animal allergens. Airborne microorganisms were collected with an air sampler and identified by microscopic and biochemical methods. Endotoxin, (1,3)-β-d-glucan, Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…This finding is largely expected and confirms the result of our previous study in which different activities were compared. Within that study, it was shown that changing cages, performed in animal rooms, and preparation of bedding and distribution of feed, performed in the storage area, are determinant factors in increasing the concentration of the airborne biocontaminants [24]. In particular, peaks of endotoxin (21.7 ng/m 3 ) were found in the storage area, while the highest concentration of the Mus m 1 allergen (61.5 ng/m 3 ) was detected in the dirty washing area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is largely expected and confirms the result of our previous study in which different activities were compared. Within that study, it was shown that changing cages, performed in animal rooms, and preparation of bedding and distribution of feed, performed in the storage area, are determinant factors in increasing the concentration of the airborne biocontaminants [24]. In particular, peaks of endotoxin (21.7 ng/m 3 ) were found in the storage area, while the highest concentration of the Mus m 1 allergen (61.5 ng/m 3 ) was detected in the dirty washing area.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the fact that, among the various activities carried out by the animal attendants, there are those performed in the storage area, which was found by the authors to be the environment most contaminated by this bio-contaminant. Bedding material, in fact, could be a significant source of accumulation and release of bacterial endotoxins [4,24,34]. Even if average doses are below the health-based recommended occupational exposure limit proposed by the Dutch Expert Committee on Occupational Safety (DECOS, 90 EU/m 3 corresponding to about 9 ng/m 3 ), two values above the limit were measured for two animal attendants (16.29 ng/m 3 and 9.12 ng/m 3 ), confirming that this work category has the highest risk of exposure to these bio-contaminants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second one, 'Application of Airborne Microorganism Indexes in Offices, Gyms, and Libraries' authored by Grisoli P. et al [15] quantified the levels of microorganisms present in the air in different places such as offices, gyms, and libraries. The third one, 'How Working Tasks Influence Biocontamination in an Animal Facility' authored by Marcelloni M. et al [16] aimed to determine what factors could be associated with a high level of exposure to biological agents in an animal facility, through the measuring and characterization of airborne fungi, bacteria, endotoxin, (1,3)-β-d-glucan and animal allergens.…”
Section: From Indoor Environment Quality Perception To Indoor Air Quamentioning
confidence: 99%